The Application of Contextual Teaching and Learning (CTL) Method to Increase Students’ English Vocabulary Mastery - Andi St. Dalaira Fezih Karimah; Kisman Salija; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The objectives of this paper were to see if using Contextual Teaching and Learning (CTL) for vocabulary instruction was helpful or not. The researchers applied a single group pre-test and post-test in a pre-experimental design. In the academic year 2021/2022, the population consisted of SMP Telkom Makassar seventh-grade students. The cluster random sampling technique was used to choose the sample, which comprised 25 students. A vocabulary test was used as a pre-test and post-test in this study. This study discovered a significant change in students' results before and after treatment. Students' pre-tests had a mean score of 70.80, which was lower than the mean score of the post-test (81.88). This study's significant value (0.000) was less than the significant level (0.05). It can be inferred that applying CTL can help seventh-grade students at SMP Telkom Makassar increase their vocabulary mastery.